Expanding Structural Space for Immunomodulatory Nucleic Acid Nanoparticles via Spatial Arrangement of Their Therapeutic Moieties. (12th August 2022) - Chandler, Morgan; Rolband, Lewis; Johnson, M. Brittany; Shi, Da; Avila, Yelixza I.; Cedrone, Edward; Beasock, Damian; Danai, Leyla; Stassenko, Elizabeth; Krueger, Joanna K.; Jiang, Jiancheng; Lee, Jeoung Soo; et al.
Abstract: Different therapeutic nucleic acids (TNAs) can be unified in a single structure by their elongation with short oligonucleotides designed to self‐assemble into nucleic acid nanoparticles (NANPs). With this approach, therapeutic cocktails with precisely controlled composition and stoichiometry of active ingredients can be delivered to the same diseased cells for enhancing pharmaceutical action. In this study, an additional nanotechnology‐based therapeutic option that enlists a biocompatible NANP‐encoded platform for their controlled patient‐specific immunorecognition is explored. For this, a set of representative functional NANPs is extensively characterized in vitro, ex vivo, and in vivo and then further analyzed for immunostimulation of human peripheral blood mononuclear cells freshly collected from healthy donor volunteers. The results of the study present the advancement of the current TNA approach toward personalized medicine and offer a new strategy to potentially address top public health challenges related to drug overdose and safety through the biodegradable nature of the functional platform with immunostimulatory regulation. Abstract : The library of nucleic acid nanoparticles (NANPs) with different numbers and orientations of functionalities is engineered and extensively characterized and tested in vitro, in vivo, and in human peripheral blood mononuclear cells  to determine NANPs immunostimulatory properties.